Strategies for Developing Household Financial Management and Strengthening Entrepreneurial Intention for Recipient Members of the Family Hope Program in West Denpasar – Bali - Made Surya PRAMANA; I Putu Iwan Pramana PUTRA; Ida Ayu Agung IDAWATI; Vital Nascimento BARRETO (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
Pemecutan Kelod is one of the villages in Denpasar city that is the target of assistance from the Indonesian government program. The assistance program provided to the Pemecutan Kelod village community is the Family Hope program. The family hope program aims to improve the welfare of the community and enable them to escape from poverty. Improving the community's abilities and skills needs to be done to maximize financial independence. This international collaborative service program aims to increase public understanding of financial literacy, financial management and interest in independent entrepreneurship. The target of this program is the community that receives assistance from the Family Hope program in Pemecutan Kelod Village, Denpasar City. The methods used were initial observation, in-depth interviews, group discussion forums, training and education, pre-tests and post-tests. The outcome and goal of this international collaborative community service program was to educate people about the importance of financial literacy in managing household and small business finances, as well as to increase community interest in entrepreneurship using their existing capital and skills. The program was successful, and post-test results indicated that the community understood the importance of financial literacy and independent entrepreneurship.